2011
DOI: 10.15407/knit2011.01.052
|View full text |Cite
|
Sign up to set email alerts
|

The study of ground-level ozone over Kyiv and its impact on public health

Abstract: Ground-level ozone in Kiev for an episode of its high concentration in August 2000 was simulated with the model of the urban air pollution UAM-V (Urban Airshed Model). The study of total ozone over Kiev and its concentration changes with height in the troposphere is made on the basis of ground-based observations with the infrared Fourier spectrometer at the Main Astronomical Observatory of National Academy of Sciences of Ukraine as a part of the ESA-NIVR-KNMI no 2907. In 2008 the satellite Aura-OMI data OMO3PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(9 reference statements)
1
0
0
Order By: Relevance
“…66 Shavrina et al in their study found that there is a significant relationship between exposure to GLO and hospital admission's increase and respiratory diseases. 85 This result is similar to result our study. Grypariset al studied the relation between health endpoints of ground level ozone in 23 European cities.…”
Section: Discussionsupporting
confidence: 93%
“…66 Shavrina et al in their study found that there is a significant relationship between exposure to GLO and hospital admission's increase and respiratory diseases. 85 This result is similar to result our study. Grypariset al studied the relation between health endpoints of ground level ozone in 23 European cities.…”
Section: Discussionsupporting
confidence: 93%